Mortality and clinical outcomes in children treated with antiretroviral therapy in four African vertical programmes during the first decade of paediatric HIV care, 2001–2010. Issue 3 (26th January 2017) - Ben‐Farhat, Jihane; Schramm, Birgit; Nicolay, Nathalie; Wanjala, Stephen; Szumilin, Elisabeth; Balkan, Suna; Pujades‐Rodríguez, Mar
Abstract: Objective: To assess mortality and clinical outcomes in children treated with antiretroviral therapy (ART) in four African vertical programmes between 2001 and 2010. Methods: Cohort analysis of data from HIV‐infected children (<15 years old) initiating ART in four sub‐Saharan HIV programmes in Kenya, Uganda and Malawi, between December 2001 and December 2010. Rates of mortality, programme attrition and first‐line clinico‐immunological failure were calculated by age group (<2, 2–4 and 5–14 years), 1 or 2 years after ART initiation, and risk factors were examined. Results: A total of 3949 children, 22.7% aged <2 years, 32.2% 2–4 years and 45.1% 5–14 years, were included. At ART initiation, 60.8% had clinical stage 3 or 4, and 46.5% severe immunosuppression. Overall mortality, attrition and 1‐year failure rates were 5.1, 10.8 and 9.0 per 100 person‐years, respectively. Immunosuppression, stage 3 or 4, and underweight were associated with increased rates of mortality, attrition and treatment failure. Adjusted estimates showed lower mortality hazard ratios (HR) among children aged 2–4 years (HR = 0.57, 95% CI 0.42–0.77 than children aged 5–14 years). One‐year treatment failure incidence rate ratios (IRR) were similar regardless of age (IRR = 0.91, 95% CI 0.67–1.25 for <2 years; 1.01, 95% CI 0.83–1.23 for 2–4 years, vs . 5–14 years). Conclusions: Good treatment outcomes were achieved during the first decade of HIV paediatric care despite the late start of therapy. Encouraging early HIV infant diagnosis in and outside prevention of mother‐to‐child transmission programmes, and linkage to care services for early ART initiation, is needed to reduce mortality and delay treatment failure.